Breakthrough waves during ventricular fibrillation depend on the degree of rotational anisotropy and the boundary conditions: a simulation study. - Ashihara T; Namba T; Ikeda T; Ito M; Kinoshita M; Nakazawa K (Journal of Cardiovascular Electrophysiology, 2001)
Introduction: The left ventricle (LV) and right ventricle (RV) are characterized by specific fiber orientation known as 'rotational anisotropy.' However, it remains unclear whether the LV and RV are different with regard to the effect of rotational anisotropy on the dynamics of scroll waves during ventricular fibrillation (VF). To resolve this issue, we used a computation-based model to study scroll wave behavior. Methods and Results: We composed an environment of simulated three-dimensional ventricular wall slabs, with optional ratios of fiber rotation to wall thickness (0°, 6°, and 12°/mm thickness; LV 10 mm, RV 5 mm), using Luo-Rudy phase I equations. When rotational anisotropy was not incorporated into the LV wall slab (endo ~ epi = 0°), most scroll waves rotated around the filament perpendicular to the tissue surface, with only a few accompanying breakthrough waves. In a twisted LV model (endo -- epi = 60° and 120°), the scroll waves were demonstrated as multiple wavelets scattered spatiotemporally, frequently accompanied by breakthrough waves that were promoted by rotational anisotropy. In a twisted RV model (endo -- epi = 30° and 60°), single scroll waves and/or figure-of-eight reentrant waves appeared, with comparatively few breakthrough waves, regardless of the degree of fiber twist. Conclusion: The proportion of electrical effects of rotational anisotropy and tissue boundaries plays an important role in the genesis of breakthrough waves during VF, and the difference in wave propagating patterns and frequency spectrum of the ventricles may arise, in part, from the number of breakthrough waves promoted by rotational anisotropy.